Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(x^3-4x^2+12x-27\)
\(=x^3-3x^2-x^2+3x+9x-27\)
\(=x^2\left(x-3\right)-x\left(x-3\right)+9\left(x-3\right)\)
\(=\left(x-3\right)\left(x^2-x+9\right)\)
1. = (x-2)^2 - y^2 = (x - 2 - y)(x-2+y)
2. = (x-y-x-y)(x-y+x+y) = 2(-y)2x = -4xy
a,\(-4x^2+4x-1\)
\(\Leftrightarrow\left(-2x-1\right)^2\)
b,\(\left(2x+1\right)^2-4\left(x-1\right)^2\)
\(\Rightarrow\left[2x+1-2\left(x-1\right)\right].\left[2x+1+2\left(x-1\right)\right]\)
\(\Rightarrow\left(2x+1-2x+2\right)\left(2x+1+2x-2\right)\)
\(\Rightarrow3\left(4x-1\right)\)
c,\(\left(2x-y\right)^2-4x^2+12x-9\)
\(\Leftrightarrow\left(2x+y\right)^2-\left(4x^2-12x+9\right)\)
\(\Leftrightarrow\left(2x+y\right)^2-\left(2x-3\right)^2\)
\(\Leftrightarrow\left(2x+y-2x+3\right)\left(2x+y+2x-3\right)\)
\(\Rightarrow\left(y+3\right)\left(4x+y-3\right)\)
d,\(\left(x+1\right)^2-4\left(x+1\right)y^2+4y^4\)
\(\Leftrightarrow\left(x+1\right)^2-2\left(x+1\right)2y^2+2^2y^4\)
\(\Leftrightarrow\left(x+1\right)^2-2\left(x+1\right)2y^2+4\left(y^2\right)^2\)
\(\Leftrightarrow\left(x+1\right)^2-2\left(x+1\right)-2y^2+\left(2y^2\right)^2\)
\(\Leftrightarrow\left(x+1-2y^2\right)^2\)
\(3\left(x^2+x+1\right)-\left(x^2+x+1\right)^2\)
\(=\left(x^2+x+1\right)\left(3-x^2-x-1\right)\)
\(=\left(x^2+x+1\right)\left(2-x^2-x\right)\)
\((x-3y)^2-2(x-3y)(x+3y)+(x+3y)^2\)
\(=(x-3y-x-3y)^2\)
=\((-6y)^2\)
\(=36y^2\)
\(x^4+x^3-4x^2+x+1\)
\(=x^4+3x^3+x^2-2x^3-6x^2-2x+x^2+3x+1\)
\(=x^2\left(x^2+3x+1\right)-2x\left(x^2+3x+1\right)+\left(x^2+3x+1\right)\)
\(=\left(x^2-2x+1\right)\left(x^2+3x+1\right)\)
\(=\left(x-1\right)^2\left(x^2+3x+1\right)\)
bắt quả tang nha